Longitudinal tracking of body composition, lower limb force-time characteristics and swimming start performance in high performance swimmers - Thng, S.; Pearson, S.; Rathbone, E.; Keogh, J. W. L. (International Journal of Sports Science & Coaching, 2022)
This study aimed to (1) track changes in body composition, lower body force-time characteristics, and swim start performance over a competitive season, and (2) investigate the intra-individual associations between changes in body composition and lower body force-time characteristics to swim start performance in five high performance swimmers (three males, two females). Over a 12-month period, body composition, lower body force-time characteristics and swim start performance were assessed at three time points via DXA scan, squat jump and swim start performance test (start times to 5 and 15 m and several kinematic and kinetic outputs). Throughout a competitive season of concurrent swimming and dry-land resistance training, improvements in lower body lean mass and squat jump force-time characteristics were observed. However, changes in start times varied between athletes. Total body and lower body lean mass both displayed large negative correlations with the time spent in the entry and propulsive underwater phases (r=0.57 to 0.66), along with a large positive correlations with glide time (r=0.56-0.53). Additionally, lower body lean mass exhibited large to very large positive correlations with the flight phase (r=0.70-0.73). Overall, these findings provide some insight into the potential magnitude of change in body composition, lower body force-time characteristics and swim start performance in high performance swimmers within a season. The large to very large correlations between increased lower body lean mass and SJ force-time metrics to improvements in aspects of start performance may provide useful information to coaches and sports scientists.